Effect of Daily Dosage of Morphine Milligram Equivalents on Free Flap Complications: A Single-Institution Retrospective Study. Issue 10 (October 2021) - Miller, Henry; Bush, Kathryn Mary; Betances, Avril; Kota, Rasagnya; Wu, Samantha; De Leo, Nicholas; Gaughan, John; Bonawitz, Steven
Summary: Introduction: There appears to be an association between preoperative opioid use and postoperative complications. We sought to determine whether patients with a history of chronic opiate use (defined as 3 months or more of sustained use) prior to undergoing free flap surgery have higher rates of 30-day complications. Methods: A retrospective review of patients undergoing free flaps from 2015 to 2020 was performed. Patient characteristics were analyzed, including daily preoperative dose of opiates, which were then converted to morphine milligram equivalents; intra-operative variables such as estimated blood loss and operating room time; and 30-day outcomes, including wound and flap complications, return to the operating room, and readmissions. Results: One hundred fifty-five patients received 160 free flaps. Of these flaps, 50/160 (31%) were performed on patients with an opiate prescription for at least three months prior to surgery. Using multivariable analysis, morphine milligram equivalents, a surrogate for opioid dose, were significantly associated with flap complications (odds ratio (OR) 1.011, 95% confidence interval (CI) 1.003–1.020, p<0.01), partial flap loss (OR 1.010, 95% CI 1.003–1.019, p<0.01), and surgical site infections (OR 1.017, 95% CI 1.007–1.027, p<0.01). Additionally, estimated blood loss was associated with partial flap loss (OR 4.838, 95% CI 1.589–14.728, p<0.006), and operating room time was also associated with flap complications (OR 1.337, 95% CI 1.152–1.150, p<0.01). Conclusion: Chronic preoperative opioid use is common for free flap surgery, and according to our single-center experience, higher daily doses are a risk factor for flap complications and surgical site infections. These findings add to the growing body of evidence that opioid use is a modifiable risk factor that may increase surgical morbidity.